Teacher Education Redefined: Contextual Cognizance and the Potential for Community Impact - Zygmunt-Fillwalk, Eva; Clark, Patricia; Clausen, Jon; Mucherah, Wilfridah (International Journal of Research on Service-Learning in Teacher Education, 2014)
This study features a paradigm in teacher education that emphasizes the context in which children grow and learn as a critical cognizance for preservice educators. Through their teacher preparation program, 46 candidates participated in an immersive semester based entirely in the community, where they completed a practicum at an elementary school or early childhood program serving low-income families. When they were not in the school, the local community center was their classroom, where they learned from community mentors about the childrens lives outside of school. Data collected yielded findings for three years of the program. Findings describe transformation of candidates and impact on the community through critical service- learning. Situated in Wengers (1998) Community of Practice framework, the proposed model of teacher education has implications for replication based on its emerging impact on teachers, schools, and communities.